2003
DOI: 10.1086/377547
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Response to the Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome Epidemic among Injection Drug Users

Abstract: The Brazilian response to the human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) epidemic is being observed all over the world because of its success. Understanding the role of injection drug users (IDUs) in the epidemic and the political response thereto is a key factor in the control of the epidemic in Brazil. This paper summarizes some of the most important analyses of the Brazilian response to the HIV/AIDS epidemic among and from IDUs. Key elements of the response include the supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1
10

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 5 publications
2
23
1
10
Order By: Relevance
“…The city of Santos in São Paulo state was the first to attempt to control the spread of HIV/AIDS between and from IDUs in 1989, and subsequently several harm reduction projects have been politically and financially supported by the federal government of Brazil. 15 Another important factor that has contributed to the decrease in HIV/AIDS and HTLV infections among IDUs is an altered pattern of drug use (from injecting cocaine to smoking crack cocaine). One study conducted in Santos during the 1990s pointed out that when cocaine injection decreased and crack cocaine use increased, the prevalence of HIV infection decreased in this geographic area.…”
Section: Discussionmentioning
confidence: 99%
“…The city of Santos in São Paulo state was the first to attempt to control the spread of HIV/AIDS between and from IDUs in 1989, and subsequently several harm reduction projects have been politically and financially supported by the federal government of Brazil. 15 Another important factor that has contributed to the decrease in HIV/AIDS and HTLV infections among IDUs is an altered pattern of drug use (from injecting cocaine to smoking crack cocaine). One study conducted in Santos during the 1990s pointed out that when cocaine injection decreased and crack cocaine use increased, the prevalence of HIV infection decreased in this geographic area.…”
Section: Discussionmentioning
confidence: 99%
“…In three different Brazilian cities (Rio de Janeiro, Salvador, and Santos), with mature epidemics (Carvalho et al 1996, Telles et al 1997, Andrade et al 1998, Guimarães et al 2001, Mesquita et al 2001) and well-established preventive programs (Telles 1999, Andrade et al 2001, Mesquita et al 2003, declining HIV/AIDS epidemics have been reported in the population of injection drug users.…”
Section: Recent Findings From Brazilian Studiesmentioning
confidence: 99%
“…With a unique drug scene, where the injection of heroin and opiates has been negligible and cocaine has been extensively snorted, smoked and, in a lesser extent, injected (Dunn & Laranjeira 1999), Brazil is nowadays the developing country with the most comprehensive network of facilities aiming to prevent drug-related harm (Mesquita et al 2003). On the other hand, studies targeting IDUs are still scarce in Brazil and evaluation of ongoing programs and projects aiming to reduce drug-related harm even rarer.…”
mentioning
confidence: 99%
“…Los 90 , el concepto de reducción de daños se va enriqueciendo con la inclusión de servicios de prevención de hepatitis y de sobredosis, prevención de la transmisión sexual y acceso y adherencia al tratamiento antirretroviral 91,92 . Estrategias como las de intervenciones de pares han sido incorporadas en el marco de programas integrales 91 Frente a situaciones problemáticas poco conocidas, los diagnósticos rápidos orientados a la acción son de utilidad.…”
Section: Programas Enfocados En Usuarios De Drogas Inyectablesunclassified